Rare-earth-doped fluoride nanoparticles with engineered long luminescence lifetime for time-gated in vivo optical imaging in the second biological window. Issue 37 (14th September 2018) - Tan, Meiling; del Rosal, Blanca; Zhang, Yuqi; Martín Rodríguez, Emma; Hu, Jie; Zhou, Zhigang; Fan, Rongwei; Ortgies, Dirk H.; Fernández, Nuria; Chaves-Coira, Irene; Núñez, Ángel; Jaque, Daniel; et al.
Abstract : We report on rare-earth-doped fluoride nanoparticles with a long lifetime and intense infrared emission in the second biological window for in vivo luminescence lifetime imaging. Abstract : Biomedicine is continuously demanding new luminescent materials to be used as optical probes for the acquisition of high resolution, high contrast and high penetration in vivo images. These materials, in combination with advanced techniques, could constitute the first step towards new diagnosis and therapy tools. In this work, we report on the synthesis of long lifetime rare-earth-doped fluoride nanoparticles by adopting different strategies: core/shell and dopant engineering. The here developed nanoparticles show intense infrared emission in the second biological window with a long luminescence lifetime close to 1 millisecond. These two properties make the here presented nanoparticles excellent candidates for time-gated infrared optical bioimaging. Indeed, their potential application as optical imaging contrast agents for autofluorescence-free in vivo small animal imaging has been demonstrated, allowing high contrast real-time tracking of gastrointestinal absorption of nanoparticles and transcranial imaging of intracerebrally injected nanoparticles in the murine brain.